Exploiting haem-iron dependence of nontypeable Haemophilus influenzae: an avenue for future therapeutic development - Brianna Atto; David A. Gell; Robyn Marsh; Robyn Marsh; Stephen Tristram (Frontiers in Cellular and Infection Microbiology)
Nontypeable Haemophilus influenzae (NTHi) is a major respiratory pathogen that imposes a substantial disease burden, globally. Further amplifying the burden of NTHi-associated infections is the rapidly expanding spectrum and prevalence of antibiotic resistance, and the lack of an effective vaccination strategy. In 2017, the World Health Organization list of “priority pathogens”, highlighted the urgent need for new therapeutic agents against NTHi. Consequently, alternative preventative or treatment approaches that do not rely on antibiotic susceptibility or stable vaccine targets are becoming more attractive. The nutritional dependency for haem/iron at all stages of NTHi pathogenesis exposes a vulnerability that may be exploited for the development of such therapies. This review explores the role of haem/iron in all facets of NTHi pathogenesis, the host-bacterial competition for this vital nutrient, and the therapeutic potential of strategies that interfere with its acquisition.